2007
DOI: 10.1507/endocrj.k06-133
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Type 5 Somatostatin Receptor in TSH-secreting Pituitary Adenomas: A Possible Marker for Predicting Long-term Response to Octreotide Therapy

Abstract: Abstract. In TSH-secreting pituitary adenomas (TSHoma), octreotide (OCT) therapy reduces tumor size and TSH secretion in some cases but not in others. As OCT acts through various types of somatostatin receptors (SSTRs), the different responses of TSHoma to OCT might be explained by the differences of SSTR expression. We therefore studied the expression of subtype-specific SSTR mRNA transcripts in tumor tissues by RT-PCR. Type 2 (SSTR2) mRNA transcripts were detected in all 8 tumors but those of SSTR3 and SSTR5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 36 publications
3
27
0
3
Order By: Relevance
“…This observation finds a molecular correlate in the previously reported functional data suggesting that SSTR5 expression influences SSTR2 internalization [24]. Moreover, the lack of SSTR5 expression has been considered the reason for the resistance to octreotide treatment and progression of tumor growth in another case of TSHoma [9]. These findings appear in line with a case of octreotide-resistant TSHoma and loss of heterozygosity at the SSTR5 locus, displaying an unusual tumor aggressiveness, which required adjuvant surgery [25].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This observation finds a molecular correlate in the previously reported functional data suggesting that SSTR5 expression influences SSTR2 internalization [24]. Moreover, the lack of SSTR5 expression has been considered the reason for the resistance to octreotide treatment and progression of tumor growth in another case of TSHoma [9]. These findings appear in line with a case of octreotide-resistant TSHoma and loss of heterozygosity at the SSTR5 locus, displaying an unusual tumor aggressiveness, which required adjuvant surgery [25].…”
Section: Discussionsupporting
confidence: 76%
“…Left panels, coronal sections; right panels, sagittal sections mechanism behind the heterogeneity of TSHoma response has not been understood yet. A recent in vivo study, analyzing two TSHoma cases, suggested that SSTR5 expression on top of SSTR2 might account for the longterm suppression of hormonal hypersecretion [9]. This observation finds a molecular correlate in the previously reported functional data suggesting that SSTR5 expression influences SSTR2 internalization [24].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…During the revision of this manuscript, similar results were reported by Yoshihara A et al showing the importance of sstr5 mRNA expression for the response to octreotide treatment [32]. This work was supported in part by a research grant from Health and Labor Sciences Research Grants, Research on Measures for Intractable Disease, Hypothalamo-Pituitary Dysfunction Research Group (to Masatomo Mori).…”
Section: Acknowledgementsupporting
confidence: 79%
“…In the case of somatotrophinomas, SSAs aimed at SSTR2 are commonly used in the pre-and post-surgical treatment to decrease GH and insulin-like growth factor 1 (IGF1) secretion and tumour size (Melmed 2009, Melmed et al 2015, Puig Domingo 2015. Additionally, thyrotroph tumours display SSTR2, SSTR3 and SSTR5 (Yoshihara et al 2007, Gatto et al 2012 and octreotide is successfully used to treat these tumours, normalizing TSH levels and decreasing tumour size (Caron et al 2001, Gatto et al 2012, van Varsseveld et al 2014.…”
Section: Somatostatin Analogues and Pituitary Adenomasmentioning
confidence: 99%